KUALITAS HIDUP IBU HAMIL DENGAN RISIKO TINGGI DI PUSKESMAS PEKAUMAN - Mariesa, Salma; Sismeri Dona; Husda Oktaviannoor (Midwifery And Complementary Care, 2022)
Background: High-risk pregnant women often report feelings of worry, fear, restless sleep, frequent headaches, low motivation for activities, and limited direct social interaction. These high-risk factors can significantly jeopardize their quality of life. Objective: This study aimed to assess the quality of life among high-risk pregnant women at the Pekauman Community Health Center. Method: This was a descriptive quantitative study that utilized a total sampling technique, including 47 respondents. Data was collected using the WHOQOL-Bref quality of life scale. Univariate analysis was employed to determine the frequency and percentage for the study variables. Results: The findings indicate that 53% of high-risk pregnant women had a good quality of life, 28% had a moderate quality of life, and 19% had a poor quality of life. The environmental domain showed the highest percentage in the "poor" category, while the social relationships domain had the highest percentage in the "good" category. The majority (53%) of high-risk pregnant women experienced a good quality of life, suggesting that they generally feel comfortable physically, psychologically, socially, and environmentally, optimally utilizing their lives for their own happiness and that of others. Keywords: Pregnant Women, Quality of Life, High Risk